Dysfunctional cardiac energy transduction, mitochondrial oxidative stress, oncogenic and apoptotic signaling in DiNP-induced asthma in murine model - Kehinde, Samuel Abiodun; Olajide, Abosede Temitope; Fatokun, Tolulope Peter; Faroud, Dalia; Hadi, Najah R.; Elgazzar, Ahmed M.; James, Adewale Segun; Ashour, Mohamed H. Mazhar (Springer, 2024)
Diisononyl phthalate (DiNP) has been associated with the development of allergies, asthma, and allergic airway inflammation. Through a complex interplay of signals and feedback mechanisms, the lungs communicate with the heart to ensure maintenance of homeostasis and supporting the body’s metabolic demands. In the current study, we assessed the crosstalk between DiNP-induced asthma and cardiac cellular respiration, oxidative stress, apoptotic potential, and induction of oncogenic factors. Ten male BALB/c mice with a weight range of 20–30 g were divided into two groups, each comprising five mice. Group 1 (control), was administered saline orally for a duration of 30 days. In contrast, group 2 (DiNP group), received 50 mg/kg of DiNP to induce asthma. After the final administration and asthma induction, the mice were euthanized, and their hearts were excised, processed, and subjected to biochemical analyses. The DiNP group had downregulated (P < 0.05) activities of the enzymes of glycolysis, tricyclic acid cycle, and electron transport chain except the hexokinase and succinate dehydrogenase activity which were upregulate relative to control. Also, oxidative distress markers (GSH, CAT, and MDA and SOD) were also perturbed. Biomarkers of inflammation (MPO and NO) were considerably higher (P < 0.05) in the heart of DiNP-induced asthma mice as compared with the control group. Furthermore, DiNP-induced asthma group has an increased cardiac caspase-3, Bax, c-Myc and K-ras, and p53 while the Bcl2 decreased when compared with control. Overall, the findings indicate that DiNP-induced asthma impairs cardiac functions by induction of key cardiac oncogenes, downregulation of cardiac energy, transduction of enzymes, and promotion of oxidative stress and cellular death. Graphical abstract: (Figure presented.).